Attention-Deficit/Hyperactivity Disorder (ADHD) and Time Perception in Adults: Do Adults with Different ADHD Symptomatology Severity Perceive Time Differently? Findings from the National Czech Study - Ptáček, Radek; Vňuková, Martina; Děchtěrenko, Filip; Weissenberger, Simon; Kitzlerová, Eva; Ptáčková, Hana; Anders, Martin (Medical Science Monitor, 2022)
BACKGROUND Studies show neurological differences between patients with attention-deficit/hyperactivity disorder (ADHD) and healthy controls. Furthermore, it is possible that poor timing is linked with impairments in neural circuitry. This study aimed to test the hypothesis that there is a difference in time perception between adults with severe ADHD symptomatology and adults with no ADHD symptomatology. MATERIAL AND METHODS Previously, we collected data from a more extensive set of participants (n=1518) concerning the prevalence of ADHD in adulthood. We recruited participants from 3 groups defined by increasing ADHD severity out of this participant pool. Each participant was presented with 2 experimental tasks (in counterbalanced order): duration estimation and duration discrimination. RESULTS In general, we did not find any specific differences in time perception related to the severity of ADHD. Regarding duration estimation, we found that the difference between the actual and estimated durations increased with the actual duration (F(1, 7028.00)=2685.38, P<0.001). Although the differences between groups were not significant, the group×duration interaction was (F[1, 7028.00]=10.86, P<0.001), with a very small effect size (ηp2<0.001, 95% CI [0.00, 0.01]). CONCLUSIONS The results suggest that although individuals may demonstrate increased ADHD symptomatology, they may not have objectively more significant difficulties in time perception tasks than their counterparts with mild symptomatology. Nonetheless, time perception should be further studied because, as qualitative research suggests, participants with more severe ADHD symptomatology subjectively perceive more significant differences in time management in real life.
Keywords: Adult; Attention Deficit Disorder with Hyperactivity; Czech Republic; dospělí; vnímání času; hyperkinetická porucha; Time Perception; prevalence; Česká republika; Humans; lidé; Prevalence